Prediksi Capaian Bulanan Pajak Daerah Kabupaten Bandung Barat Menggunakan Metode Logistic Regression - Ramdhani, Muhammad; Umbara, Fajri Rakhmat; Ilyas, Ridwan (Journal of Information System Research (JOSH), 2024)
Tax is the main source of income for the state, so that tax revenue is the biggest contributor to government agencies. However, the Regional Revenue Agency (BAPENDA) sometimes has difficulties in predicting regional monthly income. The data owned by BAPENDA is very important for estimating tax increases every month, but often these estimates are wrong. Therefore, research on predicting monthly tax ACHIEVEMENT is very helpful. Researchers consider the data mining method approach is a technique that can help BAPENDA find predictive patterns that are important for making tax increase decisions. sebumnya has predicted the results of the Ann method where for neurons 20 it produces an rmse prediction of 0.12. In this study, the logistic regression algorithm approach was used to predict regional tax achievements in West Bandung Regency. In addition, experiments were carried out to evaluate which variables affect the probability value.